Contribution of biden pilosa (blackjack) to the welfare of households in ward 23 of Mt Darwin, Zimbabwe - Mutowongi, Jessica Rutendo (BUSE, 2023)
The reliance of rural house holds on underutilised vegetables (including Biden pilosa) for sustainability is largely recognized in the literature reviews. Although the production, marketing and consuming of this vegetable have historically been not considered rural households. The consumption is high during the lean season and serves as a coping method in times of insufficiency. Hence this research study was done in Mt Darwin district aims to assess the contributions of B. pilosa to the welfare of households in ward 23. The objectives were to assess availability and accessibility, knowledge and practices, consumption preferences, the benefits as well as to investigate socioeconomic factors characterising the production of Biden Pilosa and the impact of its production on farmer welfare. The study data was collected from 45 households using a questionnaire and for triangulation key informant interviews were conducted from 3 village heads. The later were collected from other research journals and documents. Excel, SPSS 21 and content analysis was applied for data analysis. The findings indicated that that age, health and income had an impact on rate of consumption during the growing season only. The study therefore concludes that B. pilosa may be a reliable household income source. Farmers are urged to combine new technologies and local knowhow to increase the production and consumption of local vegetables. Farmers and other sectors showed do awareness education and advocacy about the welfare and trading potential of underutilized vegetables are crucial. The government extension officers need expand its technical delivery along the B. pilosa vegetables value chain. It is hoped that combined efforts will ease the commercialization of B. pilosa, thereby increasing household welfare. (B. pilosa, underutilized, welfare, socioeconomic, income)
Keywords: Biden pilosa; Black jack; Indigenous vegetables